Monitoring and physico-chemical assessment of ex-mining pools in Perak, Malaysia - Qadir, D. (Malaysian Abstracting and Indexing System, 2017)
Monitoring and Physico-chemical characterization of ex-mining pools was carried out for 9 months at 15 days interval. Physico-chemical parameters such as pH, electrical conductivity, total suspended solids (TSS), total dissolved solids (TDS), chemical oxygen demand (COD), hardness as well as anions including chloride, nitrate, phosphate, sulfate and cations such as calcium, magnesium, tin, lead, iron, nickel, chromium, zinc were investigated. A comparison was also made to National Drinking Water Quality Standards Malaysia (NDWQSM). It was determined that only turbidity, COD and cations exceeded the standard limits set for drinking water. Other parameters such as pH, electrical conductivity, anions and hardness remained within the allowable limits during the sampling period. It is revealed that COD values (up to 180 mg/L) were found above the permissible limits (10 mg/L). Moreover, among all cations investigated here, lead (up to 0.19 mg/L), nickel (up to 0.05 mg/L) and iron (up to 1.286 mg/L) were present in hazardous amount whereas tin was noted to be 25 mg/L. It was deduced that these ex-mining pools could be a potential fresh water resource only after suitable treatment such as membrane filtration and adsorption could be applied to remove the contaminants and heavy metals.